2013
DOI: 10.1371/journal.pone.0067531
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing of the Human Milk Fat Layer Transcriptome Reveals Distinct Gene Expression Profiles at Three Stages of Lactation

Abstract: Aware of the important benefits of human milk, most U.S. women initiate breastfeeding but difficulties with milk supply lead some to quit earlier than intended. Yet, the contribution of maternal physiology to lactation difficulties remains poorly understood. Human milk fat globules, by enveloping cell contents during their secretion into milk, are a rich source of mammary cell RNA. Here, we pair this non-invasive mRNA source with RNA-sequencing to probe the milk fat layer transcriptome during three stages of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
177
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(198 citation statements)
references
References 51 publications
20
177
0
1
Order By: Relevance
“…or obese. 13,14,18 Overweight BMI has also been associated with differences in prolactin response to suckling, 17 and insulin resistance is associated with both low milk supply and differences in the milk fat layer transcriptome, 19 suggesting that biological as well as sociocultural factors may affect breastfeeding success among overweight women. We also found higher rates of perceived lactation dysfunction among women with postpartum-depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…or obese. 13,14,18 Overweight BMI has also been associated with differences in prolactin response to suckling, 17 and insulin resistance is associated with both low milk supply and differences in the milk fat layer transcriptome, 19 suggesting that biological as well as sociocultural factors may affect breastfeeding success among overweight women. We also found higher rates of perceived lactation dysfunction among women with postpartum-depression symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Obesity and insulin resistance are associated with differences in prolactin levels, 17 onset of lactogensis, 18 and the human milk fat layer transcriptome. 19 In addition, in animal models, obesity is associated with poor milk production. 20 With respect to depression and lactation, women with symptoms of depression and anxiety had lower oxytocin levels during feeding in a recent study, 21 and several other neuroendocrine mechanisms may link maternal mood disorders with breastfeeding difficulties.…”
mentioning
confidence: 99%
“…In fact, insulin upregulates the expression of yϩ transport system for cationic AA, such as Lys and Arg, in mouse mammary cells (200). In a recent study carried out by RNA sequencing of milk fat layer during colostrogenesis, transition, and mature milk in two groups of women based on lactation capability, it was proposed that protein tyrosine phosphatase receptor type F (PTPRF) might be responsible for mammary insulin resistance, resulting in decreased milk yield and poor lactation (121). The study did not consider if the expression of PTPRF had any relationship with milk protein synthesis.…”
Section: Regulation Of Protein Synthesis By the Energy Content In Thementioning
confidence: 99%
“…The use of large transcriptomic analysis (i.e., microarray or RNA sequencing) by which to study the adaptation of mammary gland to lactation and/or change in milk production under specific conditions has been carried out in mouse (4,54,122,123,143,189,191,217,236,256), rat (3,47,187), bovine (31,36,56,75,96,144,183,209,218,233,239), sheep (209), goat (71,163,164), human (121,139,147), pig (204), kangaroo (120), and seal (144). It is beyond the scope of the current review to present a thorough discussion of the results from those studies.…”
mentioning
confidence: 99%
“…The present results provide the first evidence that amylin concentrations correlate with insulin concentrations in female goat neonates. Lemay et al (2013) reported that insulin has an important role in breast milk synthesis and that there is a link between insulin resistance and insufficient milk supply through the tyrosine phosphatase, receptor type, F (PTPRF) gene. The relationship between amylin and insulin concentrations in female goat neonates suggests that amylin may also be related to milk yield in later years.…”
Section: Discussionmentioning
confidence: 99%